ANALISIS PENGARUH MOTIVASI KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PADA KANTOR NOTARIS-PPAT NURDIN YUNIAR WIDIYANTO, SH.,M.Kn - Amsirun amsirun (Jurnal Strategik, 2017)
ABSTRACT This study took the title "Analysis of the Effect of Work Motivation and Work Environment on Employee Performance at the Notary Office - PPAT Nurdin Yuniar Widiyanto, SH., M.Kn". The objectives to be achieved in this study are: 1. To find out is there an effect of work motivation on employee performance at the Notary-PPAT office Nurdin Yuniar Widiyanto, SH., M.Kn. 2. To find out is there an influence of the work environment on employee performance at the Notary-PPAT office Nurdin Yuniar Widiyanto, SH., M.Kn. 3. To find out is there an effect of work motivation and work environment on employee performance at the Notary-PPAT office Nurdin Yuniar Widiyanto, SH.,M.Kn. 4. And to find out how much influence the work motivation and work environment on employee performance at the Notary-PPAT office Nurdin Yuniar Widiyanto, SH.,M.Kn. The problems in this research are: 1. Is there an effect of work motivation on employee performance at the Notary Office- PPAT Nurdin Yuniar Widiyanto, SH., M.Kn 2. Is there an influence of the work environment on employee performance at the Notary Office - PPAT Nurdin Yuniar Widiyanto, SH., M.Kn 3. Is there an effect of work motivation and work environment on employee performance at the Notary Office - PPAT Nurdin Yuniar Widiyanto, SH., M.Kn. While the hypothesis proposed is: 1. It is suspected that work motivation affects employee performance at the Notary Office - PPAT Nurdin Yuniar Widiyanto, SH., M.Kn 2. It is assumed that the work environment has an effect on employee performance at the Notary Office - PPAT Nurdin Yuniar Widiyanto, SH., M.Kn 3. It is suspected that work motivation and work environment affect employee performance at the Notary Office - PPAT Nurdin Yuniar Widiyanto, SH., M.Kn 4. It is suspected that the most influential work motivation on employee performance in the Notary Office - PPAT Nurdin Yuniar Widiyanto, SH., M.Kn The method used is a case study at the Notary Office - PPAT Nurdin Yuniar Widiyanto, SH., M.Kn, which is about the influence of work motivation, work environment and employee performance. While the analytical tools used are Validity Test, Reliability Test, Classical Assumption Test such as Multicollinearity Test, 2 Heteroscedasticity Test, Normality Test and Multiple Regression Analysis namely t Test and Test f. From the results of the analysis conclusions are taken as follows: 1. That thitung uses a confidence level of 95 percent (α / 2 = 0.05 / 2 = 0.025) and the degree of freedom of Nk (9-2) is obtained ttable of 2.447 and the results of SPSS calculation show thitung X1 = 3.198 which means that tcount> t table with a significant level of 0.019 t table with a significant level of 0.037 ftabel 4.74, so it can be concluded that the work motivation and work environment variables simultaneously or together have a significant effect on employee performance variables. 4. The f test results are known to be the value of β variable. Work motivation 0.736 which is more dominant has an effect on α of 0.05, compared to the work environment variable that β value is 0.617, so it can be concluded that the work motivation variable has a greater effect than the work environment variable at the office Notaris - PPAT Nurdin Yuniar Widiyanto, SH., M.Kn. Based on the conclusions above, the writer can provide suggestions as follows: 1. For Companies a. Motivation in work is very important, so the company is expected to always provide work motivation, pay attention to employee attendance, and provide guidance to employees and it is expected that the company will still prioritize employee welfare so that employees always improve employee performance so as to provide benefits to the company. b. A non-conducive environment can have an impact on reducing employee productivity, therefore companies need to pay attention to create a work environment and a conducive environment so that employees feel more comfortable working both physically and non-physically. While the non-physical environment can be by holding a vacation together or outbound to improve employee relations with leaders and between employees. 2. For future research a. Future research should expand the variables and measurement of research variables so that the performance of employees in the Notary Office - PPAT Nurdin Yuniar Widiyanto, SH., M.Kn can be improved. It is expected that further research can examine more about work motivation and work environment that influence employee performance at the Notary Office - PPAT 3 Nurdin Yuniar Widiyanto, SH., M.Kn in order to obtain a more complete picture, so that future research results are expected to be more both from this study.